The application of international environmental law for the achievement of environmentally sustainable tourism - Williams, Angela (2005)
This thesis analyses the relationship between tourism and the natural environment and explores ways in which the imbalance between the two may be redressed, with a view to achieving environmentally sustainable tourism. This involves a critical examination of the legal framework currently in place, so as to ascertain the relative effectiveness of presentday structures and organisations. First, both the tourism industry and the natural environment - as conceptual elements - are explored, including a review of their historical and comparative development over recent years. This provides a context within which the thesis can be placed and establishes the foundations upon which subsequent analysis may be built. Next, tourism is assessed in the context of the international legal system, in an attempt to evaluate how the international community has responded to the tourism phenomenon and, moreover, how the international legal system might apply to the various participants within the tourism industry. This provides a platform from which to evaluate, in greater detail, the applicability of international environmental law to tourism, assessing the relevant law currently regulating marine and atmospheric pollution, as well as species protection and habitat preservation. The final part of the thesis recognises the present ad hoc approach of international environmental law towards tourism, and questions whether there might exist some specific obligation for sustainable tourism within the international legal system. In order to assess this theory, the principle of sustainable development is employed as the framework concept from which sustainable tourism emanates, and allows for those various concepts which collectively constitute sustainable development to be analysed in light of sustainable tourism obligations. It is concluded that there are two primary areas where efforts to address tourism-generated environmental degradation should be concentrated. First, the World Tourism Organisation must adopt a stronger leadership position in respect of sustainable tourism and develop its role as a centralised mechanism for coordinating international and regional efforts to regulate and manage tourism activities. Secondly, there must be a concerted effort to further promote and develop the principle of `sustainable tourism', incorporating the legal rights and responsibilities embedded within this concept.